Integrasi Tasawuf Akhlaki Al-Ghazālī Dalam Keberlanjutan Lingkungan: Paradigma Spiritual Menghadapi Krisis Ekologi - Dzaky Nabil Al-Hakim; Hafizhah Nuri Rahma Mufidah; Hema Ismawati; Fauzi Annur (Ma'had Aly Idrisiyyah, 2026)
Abstract This study explores the integration of al-Ghazālī’s Sufi ethics into the framework of environmental sustainability as a spiritual and ethical paradigm addressing contemporary ecological crises. Employing an emic-oriented qualitative analytical library research methodology, the investigation examines al-Ghazālī’s seminal work, Ihya’ Ulūm al-Dīn, alongside secondary sources from accredited journals to understand how maqāmāt such as at-taubat, asy-syukr, az-zuhd, and al-mahabbah constitute an ethical transformation framework connecting spiritual, moral, and behavioral dimensions of human life. Findings indicate that pillars of environmental sustainability, including Planetary Boundaries, Life Cycle Assessment, and Sustainable Development Goals, are mutually complementary with religious agency, with Sufi ethics serving as a value-driven catalyst for ecological practices at individual, communal, and institutional levels. Universal values across faiths, including metanoia in Christianity, karma purification in Hinduism, and moral purification in Buddhism, exhibit intrinsic resonance with al-Ghazālī’s maqāmāt, facilitating interfaith collaboration in environmental stewardship. Content analysis reveals that integrating Sufi ethics promotes sustainable behavioral transformation through inner purification, gratitude, consumption restraint, and universal love, effectively addressing root causes of ecological crises such as anthropocentrism and consumerism. This study proposes an integrative conceptual model bridging spirituality, ethics, and ecology, with practical implications for religious education, governmental policy, and community engagement, emphasizing that environmental sustainability can be realized through a holistic synergy of moral, spiritual, and social dimensions. Abstrak Penelitian ini mengeksplorasi integrasi tasawuf akhlaki al-Ghazālī dalam kerangka keberlanjutan lingkungan sebagai paradigma spiritual dan etis untuk merespons krisis ekologi kontemporer. Menggunakan metodologi studi kepustakaan analitis kualitatif berbasis emic, kajian ini menelaah karya utama al-Ghazālī, Ihya’ Ulūm al-Dīn, serta literatur sekunder dari jurnal terakreditasi untuk memahami bagaimana maqāmāt seperti At-Taubat, Asy-Syukr, Az-Zuhd, dan AlMahabbah membentuk kerangka transformasi etis yang menghubungkan dimensi spiritual, moral, dan perilaku manusia. Hasil analisis menunjukkan bahwa pilar keberlanjutan lingkungan, termasuk Planetary Boundaries, Life Cycle Assessment, dan Sustainable Development Goals, saling melengkapi dengan agensi keagamaan, di mana tasawuf akhlaki berfungsi sebagai sumber nilai yang mendorong praktik ekologis pada tingkat individu, komunitas, dan institusi. Nilai-nilai universal lintas agama, seperti metanoia dalam Kristen, karma purification dalam Hindu, dan moral purification dalam Buddha, menunjukkan resonansi intrinsik dengan maqāmāt al-Ghazālī, membuka peluang kolaborasi interfaith untuk pelestarian lingkungan. Kajian ini mengungkap bahwa integrasi tasawuf akhlaki memfasilitasi perubahan perilaku berkelanjutan melalui penyucian batin, rasa syukur, pengendalian konsumsi, dan cinta universal, yang efektif menghadapi akar krisis ekologi seperti antroposentrisme dan konsumerisme. Temuan ini menawarkan model konseptual integratif antara spiritualitas, etika, dan ekologi, dengan implikasi praktis untuk pendidikan agama, kebijakan pemerintah, dan partisipasi masyarakat, sekaligus menegaskan bahwa keberlanjutan lingkungan dapat diwujudkan melalui sinergi moral, spiritual, dan sosial yang holistik.